Digging up Tyrannosaurus rex - Horner, John R.; Lessem, Don. (New York : Scholastic, 1992)
Describes the discovery and excavation of the world's only complete Tyrannosaurus fossil in Montana, and what was learned from it.
Includes bibliographical references (p. 35) and index.
G9
Keywords: Tyrannosaurus rex -- Juvenile literature; Tyrannosaurus rex; Dinosaurs; Fossils; Paleontology